High-reliability welding-resistant conductor paste and preparation method thereof

Through the combination of high-crystalline precious metal powder and lead-free microcrystalline glass powder, a high-crystalline metal film layer and a stable crystal structure are formed, which solves the problem of insufficient solder resistance and adhesion of conductor slurry, and significantly improves the welding resistance time and adhesion, the preparation of high-reliability conductor paste is achieved.

CN119296847APending Publication Date: 2025-01-10CHINA ZHENHUA GRP YUNKE ELECTRONICS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411792779.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-07
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing conductor slurry has poor solder resistance, the adhesion of the ceramic substrate thick film conductor film layer becomes worse under high temperature environment, and the welding reliability is insufficient.

Method used

The precious metal powder is used to combine 60% to 85% of precious metal powder, 15.0% to 35.8% of organic carrier and 1.0% to 8.0% of lead-free microcrystalline glass powder. The precious metal powder is silver powder, silver palladium powder, platinum powder, etc. The body shape is spherical or sheet-like. By combining high crystallinity and lead-free microcrystalline glass powder, a high crystalline metal film layer and a stable crystal structure are formed, thereby improving the solder resistance and adhesion of the conductor slurry.

Benefits of technology

The solder resistance time of the conductor slurry is significantly improved, the solder resistance time is extended by 10S to 30S, and the adhesion is improved after environmental tests, ensuring the stability and reliability of the slurry film layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119296847A_ABST
    Figure CN119296847A_ABST
Patent Text Reader

Abstract

The invention discloses high-reliability welding-resistant conductor paste and a preparation method thereof, and belongs to the technical field of electronic paste. The conductive paste comprises precious metal powder, an organic carrier and lead-free microcrystalline glass powder. The noble metal powder is one or a mixture of more of silver powder, silver-palladium powder and platinum powder, and the metal powder is spherical, spheroidal or flaky; the organic carrier comprises the following components: resin, a solvent and an auxiliary agent; the basic components of the lead-free microcrystalline glass powder are Bi2O3, TiO2 and SiO2, and the added components of the lead-free microcrystalline glass powder are one or more of B2O3, CaO, CuO, Li2O, MgO and Al2O3. The preparation method comprises an organic carrier preparation method, a lead-free microcrystalline glass powder preparation method and a slurry preparation method. The problems that existing conductor paste is poor in welding resistance, adhesive force becomes poor after an environment experiment of a ceramic substrate thick film conductor film layer, and welding reliability is poor are solved. The conductive paste is widely applied to high-reliability conductive paste.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electronic pastes, and further relates to the technical field of conductor pastes, and specifically, to a highly reliable and solder-resistant conductor paste and a preparation method thereof. Background Art

[0002] In recent years, science and technology have developed rapidly. Systems and complete machines have increasingly higher requirements for the volume, weight, precision, reliability and other performance of integrated circuits. In particular, there is an urgent demand for high-performance, multi-functional, high-density, customized thick-film hybrid integrated circuits. At the same time, electronic components are also developing in three directions: high precision and miniaturization, substrate integration, and material diversification. These have put forward higher requirements on the ability of high-end electronic pastes to work stably in high-temperature environments.

[0003] Thick film hybrid integrated circuits are made by printing conductor paste, resistor paste, insulation paste, etc. into patterns on ceramic substrates using screen printing technology, and then forming circuit connections through high temperature sintering. The conductor paste mainly plays the role of conduction and welding. In the process of thick film hybrid integrated circuits, products are usually repeatedly welded on the thick film conductor welding layer. And because thick film hybrid integrated circuits are often used in high temperature environments, the conductor paste is required to have excellent conductivity, high adhesion, good environmental stability and other requirements.

[0004] The existing conductor paste is usually made of a uniform mixture of metal powder and inorganic binder, and is sintered at high temperature to form a conductive film attached to the ceramic substrate. The conductor paste made in the prior art, such as the patent CN112951479A, has poor solder resistance and a short solder resistance time, usually about 20 seconds. After environmental testing, the adhesion becomes poor, and the electrode film layer falls off.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The technical problem to be solved by the present invention is to solve the problems of poor solder resistance of the existing conductor paste, poor adhesion of the thick film conductor film layer of the ceramic substrate after environmental testing, and poor welding reliability.

[0007] To this end, the present invention provides a high-reliability solder-resistant conductor paste. The mass percentage components of the conductor paste include: 60% to 85% precious metal powder, 15.0% to 35.8% organic carrier, 1.0% to 8.0% lead-free microcrystalline glass powder.

[0008] The precious metal powder is a mixture of one or more of silver powder, silver palladium powder, platinum powder, etc., and the powder shape is spherical, quasi-spherical or flake. The particle size of the silver powder, silver palladium powder and platinum powder is 0.2µm to 7µm, and the specific surface area is 0.5m 2 / g~6m 2 / g, tap density is 2g / cm 3 ~6g / cm 3 , so that the metal powder has high crystallinity, thereby improving the solder resistance of the conductor paste. Due to the high crystallinity of the metal powder, it is easy to form a high crystallinity metal film layer during its sintering process. This metal film layer has a dense structure, and due to the binding effect of the lattice, it reduces its migration rate in the tin solder, thereby improving the solder resistance of the metal film layer.

[0009] The components of the organic carrier include resin, solvent and auxiliary agent. The resin is a mixture of one or more resins selected from ethyl cellulose, cellulose acetate, acrylic resin, phenolic resin, epoxy resin, modified epoxy resin, polymethyl methacrylate, polyvinyl butyral, etc.; the solvent is a mixture of one or more solvents selected from terpineol, diethylene glycol butyl ether, diethylene glycol butyl ether acetate, alcohol ester twelve, DBE, dibutyl phthalate, diethylene glycol monomethyl ether, dimethyl phthalate, tributyl citrate, ethylene glycol ethyl ether acetate, stearic acid, isophorone, hydrogenated terpineol, etc.; the auxiliary agent is a mixture of one or more auxiliary agents selected from hydrogenated castor oil, soybean lecithin, organic bentonite, fumed silica, polyamide wax, organic siloxane, etc.

[0010] The basic components of the lead-free microcrystalline glass powder are Bi2O3, TiO2, and SiO2, and the added components are one or more of B2O3, CaO, CuO, Li2O, MgO, Al2O3, etc. The particle size of the lead-free glass powder is ≤10µm, and the softening point is 700℃~900℃.

[0011] Preferably, the mass percentage components of the lead-free microcrystalline glass powder are: 15% to 40% Bi2O3, 5% to 30% TiO2, 5% to 20% SiO2, 5% to 20% B2O3, 2% to 16% CaO, 3% to 15% CuO, 1% to 8% Li2O, 1% to 15% MgO, and 1% to 8% Al2O3.

[0012] The method for preparing a high-reliability solder-resistant conductor paste comprises the following method: (1) Preparation method of organic carrier: weigh the raw materials, including solvent, resin, additive, etc. according to the organic carrier formula, mix the raw materials, heat to 50°C to 150°C to dissolve them until there is no obvious solute in the carrier. After the dissolution is completed, filter out impurities with filter cloth and place at room temperature for use.

[0013] (2) Preparation method of lead-free microcrystalline glass powder: Weigh the raw materials according to the formula of lead-free microcrystalline glass powder, use a powder grinder to mix 3 to 8 times, each time for 1 min to 5 min. After mixing evenly, use a crucible to put it into a melting furnace and melt it at 900℃ to 1400℃ for 1h to 4h. After melting, pour it out at high temperature and quench it with water, and ball mill it for 8h to 36h until the particle size of the glass powder meets the use standard.

[0014] (3) Slurry preparation method: The metal powder, lead-free microcrystalline glass powder and organic carrier are weighed according to mass percentage and uniformly mixed, and dispersed evenly using a three-roll mill until the fineness of the test conductor slurry is ≤15µm.

[0015] Compared with the prior art, the highly reliable solder-resistant conductor paste of the present invention has the following advantages: (1) The present invention uses high-crystallinity metal powder, which significantly improves the solder resistance of the conductor paste. The solder resistance time is increased from 20 seconds of the previous product to 30 seconds to 50 seconds, which means that the solder resistance time is extended by 10 seconds to 30 seconds. The principle is that high-crystallinity metal powder is easy to form a high-crystallinity metal film layer during its sintering process. This metal film layer has a dense structure, and due to the binding effect of the lattice, its migration rate in the tin solder is reduced, thereby improving the solder resistance of the metal film layer.

[0016] (2) TiO2 and Li2O in the glass powder of the present invention can effectively promote the crystallization of the glass body to form a lead-free microcrystalline glass with an inorganic bonding phase. The crystal structure formed in the glass body is usually in the shape of strips or small squares. This crystal structure in the glass helps to overlap into the skeleton of the slurry, and then the film structure is more stable, making the slurry more stable during the environmental test, reducing the risk of structural collapse, and improving the adhesion after the environmental test. In addition, SiO2 in the glass also has certain solder resistance properties, which is used to improve the solder resistance of the slurry.

[0017] Therefore, the conductor paste of the present invention has good solder resistance and high reliability, can ensure the adhesion of the paste film after environmental testing, and can be widely used in high-reliability conductor pastes. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a schematic diagram of XRD of high crystalline silver powder in Example 1.

[0019] Figure 2 This is a schematic diagram of the electron microscope of the highly crystalline silver powder in Example 1.

[0020] Figure 3 This is a schematic diagram of the electron microscope of the lead-free microcrystalline glass powder in Example 1. DETAILED DESCRIPTION

[0021] The highly reliable solder-resistant conductor paste and its preparation method, the specific implementation cases are as follows: Embodiment 1:

[0022] The conductive paste includes the following components in percentage by mass: 75% of spherical silver powder, 3.5% of lead-free microcrystalline glass, and 21.5% of an organic carrier.

[0023] The particle size of the silver powder is 0.2µm to 4µm, and the specific surface area is 1.5m 2 / g, tap density is 3.5g / cm 3 .

[0024] The organic carrier component includes 24.8% of pineol, 8.5% of dibutyl phthalate, 8.6% of ethyl cellulose, 13.4% of acrylic resin, 5.7% of soybean lecithin, 15.3% of ethylene glycol ethyl ether acetate, and 20% of alcohol ester dodecahydrate.

[0025] The components of the inorganic microcrystalline glass powder include 30.5% Bi2O3, 8.3% SiO2, 10.5% B2O3, 10% CuO, 8% CaO, 15.2% TiO2, 5.7% Li2O, and 11.8% MgO. The particle size of the glass powder is ≤5µm, and the softening point is 780°C to 850°C.

[0026] The preparation method of the conductor slurry is as follows: (1) Preparation of organic carrier: Raw materials, including solvent, resin, additives, etc., are weighed according to the organic carrier formula. After mixing the raw materials, they are heated to 100° C. to dissolve until there is no obvious solute in the carrier. After the dissolution is completed, impurities are filtered out with filter cloth and placed at room temperature for use.

[0027] (2) Preparation of lead-free microcrystalline glass powder: Weigh the raw materials according to the formula of lead-free microcrystalline glass powder, use a powder grinder to mix 5 times, each time for 2 minutes. After mixing evenly, put it into a crucible and put it into a melting furnace to melt at 1000℃ for 2 hours. After the melting is completed, pour it out at high temperature and quench it with water. Ball mill it for 20 hours. The particle size of the tested glass powder is ≤5µm.

[0028] (3) Slurry preparation: The metal powder, lead-free microcrystalline glass powder, organic carrier and additive are uniformly mixed and dispersed using a three-roll mill. The fineness of the conductor slurry is tested to be ≤8µm. Embodiment 2:

[0029] The conductive paste includes the following components in percentage by mass: 70% of spherical silver palladium powder, 2.8% of lead-free microcrystalline glass, and 27.2% of an organic carrier.

[0030] The particle size of the silver palladium powder is 0.5 μm to 1.5 μm, and the specific surface area is 2.8 m 2 / g, tap density is 2.7g / cm 3.

[0031] The organic carrier component includes 24.8% of stearic acid, 2.5% of fumed silica, 12.6% of cellulose acetate, 10.5% of polyvinyl butyral, 5.7% of dimethyl phthalate, 8.5% of ethylene glycol ethyl ether acetate, 5.9% of tributyl citrate, and 7.4% of polyamide wax.

[0032] The components of the inorganic microcrystalline glass powder include 27.1% Bi2O3, 13.4% SiO2, 11.5% B2O3, 17.3% TiO2, 10.6% Li2O, and 20.1% MgO. The particle size of the glass powder is 3µm to 6µm, and the softening point is 780°C to 900°C.

[0033] The preparation method of the conductor slurry is as follows: (1) Preparation of organic carrier: Raw materials, including solvent, resin, additive, etc., are weighed according to the organic carrier formula. After mixing the raw materials, they are heated to 80° C. to dissolve until there is no obvious solute in the carrier. After the dissolution is completed, impurities are filtered out with filter cloth and placed at room temperature for use.

[0034] (2) Preparation of lead-free microcrystalline glass powder: Weigh the raw materials according to the formula of lead-free microcrystalline glass powder, use a powder grinder to mix 8 times, each time for 2 minutes. After mixing evenly, put it into a crucible and put it into a melting furnace to melt at 1100°C for 3 hours. After melting, pour it out at high temperature and quench it with water. Ball mill it for 20 hours. The particle size of the tested glass powder is ≤6µm.

[0035] (3) Slurry preparation: The metal powder, lead-free microcrystalline glass powder, organic carrier and additive are uniformly mixed and dispersed using a three-roll mill. The fineness of the conductor slurry is tested to be ≤5µm. Embodiment 3:

[0036] The conductor paste includes the following components in percentage by mass: 70% of spherical silver powder, 8% of spherical platinum powder, 2.5% of lead-free microcrystalline glass, and 17% of an organic carrier.

[0037] The particle size of the silver powder is 0.4µm to 2µm, and the specific surface area is 1.5m 2 / g, tap density is 3.5g / cm 3 .

[0038] The particle size of the platinum powder is 0.4µm to 1.8µm, and the specific surface area is 1.7m 2 / g, tap density is 5.3g / cm 3 .

[0039] The organic carrier component comprises 15.2% of polymethyl methacrylate, 2.1% of hydrogenated castor oil, 5.6% of organosiloxane, 23.4% of ethylene glycol ethyl ether acetate, 32.7% of polyvinyl butyral, 4.3% of ethyl cellulose and 16.7% of alcohol ester dodecahydrate.

[0040] The inorganic microcrystalline glass powder comprises 28.0% Bi2O3, 20.4% SiO2, 24.7% B2O3, 13.5% CaO, 8.9% TiO2 and 4.5% MgO. The particle size of the glass powder is ≤7µm and the softening point is 730°C to 850°C.

[0041] The preparation method of the conductor slurry is as follows: (1) Preparation of organic carrier: Raw materials, including solvent, resin, additives, etc., are weighed according to the organic carrier formula. After mixing the raw materials, they are heated to 110° C. to dissolve until no obvious solute is left in the carrier. After dissolution is complete, impurities are filtered out using filter cloth and the mixture is placed at room temperature for later use.

[0042] (2) Preparation of lead-free microcrystalline glass powder: Weigh the raw materials according to the formula of lead-free microcrystalline glass powder, use a powder grinder to mix 6 times, each time for 3 minutes. After mixing evenly, put it into a crucible and put it into a melting furnace to melt at 1300℃ for 3 hours. After melting, pour it out at high temperature and quench it with water. Ball mill it for 16 hours. The particle size of the tested glass powder is ≤7µm.

[0043] (3) Slurry preparation: The metal powder, lead-free microcrystalline glass powder, organic carrier and additive are uniformly mixed and dispersed using a three-roll mill. The fineness of the conductor slurry is tested to be ≤10µm. Embodiment 4:

[0044] The conductive paste includes the following components in percentage by mass: 50% of spherical silver powder, 17% of flaky silver powder, 5.0% of lead-free microcrystalline glass, and 28% of an organic carrier.

[0045] The particle size of the spherical silver powder is 0.3µm to 1.86µm, and the specific surface area is 3.7m 2 / g, tap density is 2.6g / cm 3 , burn loss 1.36%.

[0046] The particle size of the flaky silver powder is 1.5µm to 5.42µm, and the specific surface area is 1.57m 2 / g, tap density is 2.6g / cm 3 , burn loss 0.47%.

[0047] The organic carrier component comprises 32.7% of terpineol, 12.3% of ethyl cellulose, 23.8% of cellulose acetate, 17.1% of DBE, 6.7% of tributyl citrate and 7.4% of organic bentonite.

[0048] The inorganic microcrystalline glass powder has components of 37.5% Bi2O3, 15.8% SiO2, 26.4% TiO2, 6.6% Al2O3, and 13.7% B2O3. The particle size of the glass powder is ≤6.5µm, and the softening point is 780°C to 870°C.

[0049] The preparation method of the conductor slurry is as follows: (1) Preparation of organic carrier: Raw materials, including solvent, resin, additives, etc., are weighed according to the organic carrier formula. After mixing the raw materials, they are heated to 110° C. to dissolve until no obvious solute is left in the carrier. After dissolution is complete, impurities are filtered out using filter cloth and the mixture is placed at room temperature for later use.

[0050] (2) Preparation of lead-free microcrystalline glass powder: Weigh the raw materials according to the formula of lead-free microcrystalline glass powder, use a powder grinder to mix 8 times, each time for 2 minutes. After mixing evenly, put it into a crucible and put it into a melting furnace for melting at 1150°C for 4 hours. After melting, pour it out at high temperature and quench it with water. Ball mill it for 24 hours. The particle size of the tested glass powder is ≤6.5µm.

[0051] (3) Slurry preparation: The metal powder, lead-free microcrystalline glass powder, organic carrier and additive are uniformly mixed and dispersed using a three-roll mill. The fineness of the conductor slurry is tested to be ≤7µm.

[0052] The solder resistance and reliability of the conductor pastes prepared in Examples 1 to 4 were tested. The specific methods are as follows: the solder resistance test method refers to GBT 17473.7-2008 Test method for precious metal pastes for microelectronics technology, where the solder resistance test is measured by time until the solder area is ≤9 / 10; the adhesion test method refers to GBT 17473.4-2008 Test method for precious metal pastes for microelectronics technology, where the aging adhesion test is to place the product with soldered leads in an environment of 150℃@1000 h and perform the test after aging. The results are shown in Table 1 below: Table 1 Slurry test results of Examples 1 to 4

[0053] It can be seen from the results in Table 1 that compared with Example 3 of the prior art patent CN112951479A, the soldering resistance time of the conductor paste described in the present invention is increased from the original 20S to 30S~50S, and the soldering resistance time is extended by 10S~30S; the aging adhesion of the conductor paste is increased by 4.9N~17.0N.

[0054] The X-ray diffraction (XRD) test results of the high crystalline silver powder in Example 1 are as follows: Figure 1 shown.

[0055] The scanning electron microscope (SEM) image results of the high crystalline silver powder in Example 1 are as follows: Figure 2 shown.

[0056] The scanning electron microscope (SEM) image results of the lead-free microcrystalline glass powder in Example 1 are as follows: Figure 3 shown.

[0057] Depend on Figure 1-3 It is further shown that the structure of high-crystalline silver powder and lead-free microcrystalline glass powder plays a fundamental role in improving the solder resistance of conductor paste and the adhesion under environmental tests.

[0058] In summary, the slurry of the present invention increases the solder resistance of the slurry by selecting high-crystallinity metal powder; and improves the crystallization performance of the glass powder by studying the glass powder formula. The lead-free microcrystalline glass powder in the present invention precipitates stable crystals during the slurry sintering process and forms a skeleton in the slurry to improve the stability of the slurry in a high temperature environment. Referring to the test results of Examples 1 to 4, the solder resistance of the slurry and the adhesion under environmental tests have been significantly improved, solving the problems of poor solder resistance and poor adhesion after environmental tests in the prior art.

[0059] The invention has good solder resistance and high reliability, and can ensure the adhesion of the slurry film layer after environmental testing.

[0060] Finally, it should be noted that the above embodiments are merely examples for the purpose of clear explanation. The present invention includes but is not limited to the above embodiments. It is not necessary and impossible to list all implementation methods exhaustively. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. All implementation methods that meet the requirements of the present invention belong to the protection scope of the present invention.

Claims

1. A highly reliable solder-resistant conductor paste, characterized in that: By mass percentage, the components of the conductive paste include: 60% to 85% precious metal powder, 15.0% to 35.8% organic carrier, 1.0% to 8.0% lead-free microcrystalline glass powder; The precious metal powder is a mixture of one or more of silver powder, silver palladium powder and platinum powder. The shape of the metal powder is spherical, quasi-spherical or flake-shaped. The particle size of the silver powder, silver palladium powder and platinum powder is 0.2µm to 7µm, and the specific surface area is 0.5m 2 / g~6m 2 / g, tap density is 2g / cm 3 ~6g / cm 3 ; The components of the organic carrier include resin, solvent, and auxiliary agent. The resin is a mixture of one or more of ethyl cellulose, cellulose acetate, acrylic resin, phenolic resin, epoxy resin, modified epoxy resin, polymethyl methacrylate, and polyvinyl butyral; the solvent is a mixture of one or more of terpineol, diethylene glycol butyl ether, diethylene glycol butyl ether acetate, alcohol ester twelve, DBE, dibutyl phthalate, diethylene glycol monomethyl ether, dimethyl phthalate, tributyl citrate, ethylene glycol ethyl ether acetate, stearic acid, isophorone, and hydrogenated terpineol; the auxiliary agent is a mixture of one or more of hydrogenated castor oil, soybean lecithin, organic bentonite, fumed silica, polyamide wax, and organic siloxane; The basic components of the lead-free microcrystalline glass powder are Bi2O3, TiO2, and SiO2, and the added components are one or more of B2O3, CaO, CuO, Li2O, MgO, and Al2O3; the particle size of the lead-free glass powder is ≤10µm, and the softening point is 700℃~900℃.

2. A highly reliable solder-resistant conductive paste as claimed in claim 1, characterized in that: The mass percentage components of the lead-free microcrystalline glass powder are: 15%~40% Bi2O3, 5%~30% TiO2, 5%~20% SiO2, 5%~20% B2O3, 2%~16% CaO, 3%~15% CuO, 1%~8% Li2O, 1%~15% MgO, 1%~8% Al2O3.

3. The method for preparing a highly reliable solder-resistant conductive paste according to claim 1, characterized in that: The following methods are included: (1) Preparation method of organic carrier: weigh raw materials including solvent, resin and additive according to the organic carrier formula, mix the raw materials, heat to 50°C to 150°C to dissolve until there is no obvious solute in the carrier, filter impurities with filter cloth after dissolution, and place at room temperature for use; (2) Preparation method of lead-free microcrystalline glass powder: weigh the raw materials according to the formula of lead-free microcrystalline glass powder, use a powder grinder to mix 3 to 8 times, each time for 1 min to 5 min, after mixing evenly, use a crucible to put it into a melting furnace at 900°C to 1400°C for 1h to 4h, pour it out at high temperature after melting, quench it with water, and ball mill it for 8h to 36h until the particle size of the glass powder meets the set standard; (3) Slurry preparation method: The metal powder, lead-free microcrystalline glass powder and organic carrier are weighed according to mass percentage and uniformly mixed, and dispersed evenly using a three-roll mill until the fineness of the test conductor slurry is ≤15µm.

4. A highly reliable solder-resistant conductor paste as claimed in claim 1, characterized in that: By mass percentage, the components of the conductive paste include: 75% spherical silver powder, 3.5% lead-free microcrystalline glass, 21.5% organic carrier; The particle size of the silver powder is 0.2µm to 4µm, and the specific surface area is 1.5m 2 / g, tap density is 3.5g / cm 3 ; The components of the organic carrier include 24.8% of pineol, 8.5% of dibutyl phthalate, 8.6% of ethyl cellulose, 13.4% of acrylic resin, 5.7% of soybean lecithin, 15.3% of ethylene glycol ethyl ether acetate, and 20% of alcohol ester dodecahydrate; The components of the inorganic microcrystalline glass powder include 30.5% Bi2O3, 8.3% SiO2, 10.5% B2O3, 10% CuO, 8% CaO, 15.2% TiO2, 5.7% Li2O, and 11.8% MgO; the particle size of the glass powder is ≤5µm, and the softening point is 780°C to 850°C.

5. The method for preparing a highly reliable solder-resistant conductive paste according to claim 4, characterized in that: The specific preparation method is as follows: (1) Preparation method of organic carrier: weigh raw materials including solvent, resin and additive according to the organic carrier formula, mix the raw materials, heat to 100°C to dissolve until no obvious solute is left in the carrier, filter impurities with filter cloth after dissolution, and place at room temperature for use; (2) Preparation method of lead-free microcrystalline glass powder: weigh the raw materials according to the formula of lead-free microcrystalline glass powder, use a powder grinder to mix 5 times, each time for 2 minutes, after mixing evenly, use a crucible to put it into a melting furnace and melt it at 1000℃ for 2 hours. After the melting is completed, pour it out at high temperature and quench it with water, ball mill it for 20 hours, and test the particle size of the glass powder to be ≤5µm; (3) Slurry preparation method: The metal powder, lead-free microcrystalline glass powder, organic carrier and additive are uniformly mixed and dispersed evenly using a three-roll mill. The fineness of the conductor slurry is tested to be ≤8µm.

6. A highly reliable solder-resistant conductive paste as claimed in claim 1, characterized in that: By mass percentage, the components of the conductive paste include: 70% spherical silver palladium powder, 2.8% lead-free microcrystalline glass, 27.2% organic carrier; The particle size of the silver palladium powder is 0.5 μm to 1.5 μm, and the specific surface area is 2.8 m 2 / g, tap density is 2.7g / cm 3 ; The components of the organic carrier include 24.8% stearic acid, 2.5% fumed silica, 12.6% cellulose acetate, 10.5% polyvinyl butyral, 5.7% dimethyl phthalate, 8.5% ethylene glycol ethyl ether acetate, 5.9% tributyl citrate, and 7.4% polyamide wax; The components of the inorganic microcrystalline glass powder include 27.1% Bi2O3, 13.4% SiO2, 11.5% B2O3, 17.3% TiO2, 10.6% Li2O, and 20.1% MgO; the particle size of the glass powder is 3µm to 6µm, and the softening point is 780°C to 900°C.

7. The method for preparing a highly reliable solder-resistant conductive paste according to claim 6, characterized in that: The specific preparation method is as follows: (1) Preparation method of organic carrier: weigh raw materials including solvent, resin and additive according to the organic carrier formula, mix the raw materials, heat to 80°C to dissolve until no obvious solute is left in the carrier, filter impurities with filter cloth after dissolution, and place at room temperature for use; (2) Preparation method of lead-free microcrystalline glass powder: weigh the raw materials according to the formula of lead-free microcrystalline glass powder, use a powder grinder to mix 8 times, each time for 2 minutes, after mixing evenly, use a crucible to put it into a melting furnace and melt it at 1100℃ for 3 hours. After the melting is completed, pour it out at high temperature and quench it with water, ball mill it for 20 hours, and test the particle size of the glass powder to be ≤6µm; (3) Slurry preparation method: The metal powder, lead-free microcrystalline glass powder, organic carrier and additive are uniformly mixed, and dispersed evenly using a three-roll mill. The fineness of the conductor slurry is tested to be ≤5µm.

8. The highly reliable solder-resistant conductive paste according to claim 1, characterized in that: By mass percentage, the components of the conductive paste include: 70% spherical silver powder, 8% spherical platinum powder, 2.5% lead-free microcrystalline glass, 17% organic carrier; The particle size of the silver powder is 0.4µm to 2µm, and the specific surface area is 1.5m 2 / g, tap density is 3.5g / cm 3 ; The particle size of the platinum powder is 0.4µm to 1.8µm, and the specific surface area is 1.7m 2 / g, tap density is 5.3g / cm 3 ; The organic carrier comprises 15.2% polymethyl methacrylate, 2.1% hydrogenated castor oil, 5.6% organosiloxane, 23.4% ethylene glycol ethyl ether acetate, 32.7% polyvinyl butyral, 4.3% ethyl cellulose, and 16.7% alcohol ester dodecahydrate; The inorganic microcrystalline glass powder comprises 28.0% Bi2O3, 20.4% SiO2, 24.7% B2O3, 13.5% CaO, 8.9% TiO2 and 4.5% MgO; the particle size of the glass powder is ≤7µm and the softening point is 730°C to 850°C.

9. The method for preparing a highly reliable solder-resistant conductive paste according to claim 8, characterized in that: Specific preparation method (1) Preparation method of organic carrier: weigh raw materials including solvent, resin and additive according to the organic carrier formula, mix the raw materials, heat to 110°C to dissolve until no obvious solute is left in the carrier, filter impurities with filter cloth after dissolution, and place at room temperature for use; (2) Preparation method of lead-free microcrystalline glass powder: weigh the raw materials according to the formula of lead-free microcrystalline glass powder, use a powder grinder to mix 6 times, each time for 3 minutes, after mixing evenly, use a crucible to put it into a melting furnace and melt it at 1300℃ for 3 hours. After the melting is completed, pour it out at high temperature and quench it with water, ball mill it for 16 hours, and test the particle size of the glass powder to be ≤7µm; (3) Slurry preparation method: The metal powder, lead-free microcrystalline glass powder, organic carrier and additive are uniformly mixed, and dispersed evenly using a three-roll mill. The fineness of the conductor slurry is tested to be ≤10µm.

10. The highly reliable solder-resistant conductive paste according to claim 1, characterized in that: By mass percentage, the components of the conductive paste include: 50% spherical silver powder, 17% flake silver powder, 5.0% lead-free microcrystalline glass, 28% organic carrier; The particle size of the spherical silver powder is 0.3µm to 1.86µm, and the specific surface area is 3.7m 2 / g, tap density is 2.6g / cm 3 , burn loss 1.36%; The particle size of the flaky silver powder is 1.5 μm to 5.42 μm, and the specific surface area is 1.57 m 2 / g, tap density is 2.6g / cm 3 , burn loss 0.47%; The components of the organic carrier are 32.7% terpineol, 12.3% ethyl cellulose, 23.8% cellulose acetate, 17.1% DBE, 6.7% tributyl citrate, and 7.4% organic bentonite; The inorganic microcrystalline glass powder has a composition of 37.5% Bi2O3, 15.8% SiO2, 26.4% TiO2, 6.6% Al2O3, and 13.7% B2O3; the glass powder has a particle size of ≤6.5µm and a softening point of 780°C to 870°C; The specific preparation method of the conductor slurry is as follows: (1) Preparation method of organic carrier: weigh raw materials including solvent, resin and additive according to the organic carrier formula, mix the raw materials, heat to 110°C to dissolve until no obvious solute is left in the carrier, filter impurities with filter cloth after dissolution, and place at room temperature for use; (2) Preparation method of lead-free microcrystalline glass powder: weigh the raw materials according to the formula of lead-free microcrystalline glass powder, use a powder grinder to mix 8 times, each time for 2 minutes, after mixing evenly, use a crucible to put it into a melting furnace and melt it at 1150°C for 4 hours. After the melting is completed, pour it out at high temperature and quench it with water, ball mill it for 24 hours, and test the particle size of the glass powder to be ≤6.5µm; (3) Slurry preparation method: The metal powder, lead-free microcrystalline glass powder, organic carrier and additive are uniformly mixed, and dispersed evenly using a three-roll mill. The fineness of the conductor slurry is tested to be ≤7µm.